QUALITY BY DESIGN-GUIDED WHITE AND GREEN HPLC METHOD FOR THE DETERMINATION OF PROCESS-RELATED IMPURITIES OF ELACESTRANT IN BULK DRUG AND PHARMACEUTICAL FORMULATIONS - KUMAR SISTA, VENKATA SAI SURESH; JHA, ANJALI; HARAN A., VLNSH HARI (International Journal of Applied Pharmaceutics, 2026)
Objective: The quality by design (QbD) guided, robust, and environmentally sustainable HPLC method was developed for the simultaneous quantification of elacestrant and its process-related impurities. Methods: The method optimisation uses organic solvent composition, mobile phase pH, and flow rate as critical method parameters. Based on structural features and pKa values of the analytes, separation was achieved on a hypersilgold C18 (250×4.6 mm, 5 µm) column using a green mobile phase of ethanol and 0.1% aqueous formic acid (65:35, v/v) at pH 3.4 at a 0.7 ml/min flow rate, achieving baseline resolution between elacestrant and its close eluting dihydrochloride impurity ( = 3.1) with good symmetry (tailing factor ~1.1) and a total run time of 13 min. Results: The method validation demonstrates excellent linearity (r²>0.999), accuracy (recoveries 99–101%), precision (RSD<1.5%), and sensitivity (LOQs 0.1–0.2 µg/ml for impurities). The sustainability assessment confirms the strong environmental and operational profile of the method. The AGREE evaluation yields a score of 0.78, whereas the GAPI pictogram displays predominantly green fields, confirming the strong alignment of the proposed method with green analytical chemistry principles. Further, the RGB12 model demonstrates favourable scores of 73.2% (redness), 75.8% (greenness), and 86.7% (blueness) with an integrated whiteness score of 78.3%. These results classify the proposed method as a white analytical procedure. Conclusion: Collectively, these outcomes confirm that the developed method was not only analytically reliable but also environmentally responsible and economically feasible. Hence, the method was highly suitable for routine impurity profiling and sustainable quality control of elacestrant in pharmaceutical formulations.